Democratic regression in Asia: introduction. Issue 1 (2nd January 2021) - Croissant, Aurel; Haynes, Jeffrey
ABSTRACT: Given Asia-Pacific's diversity and the large variance of potentially relevant causal factors, the region presents social scientists with a natural laboratory to test competing theories of democratic erosion, decay and revival and to identify new patterns and relationships. This introductory article offers a brief review of the relevant literature and introduces the different categories of analysis that build the analytical framework considered in various forms in the special issue. The article discusses the reasons for the renewed pessimism in democratization and democracy studies and provides a survey of different conceptualizations intended to capture forms of democratic regression and the autocratization concept to which the contributors to this special issue adhere. We discuss how Asia-Pacific experiences fit into the debate about democracy's deepening global recession and examine assumptions about the causes, catalysts and consequences of democratic regression and resilience in the comparative politics literature. Finally, the remaining twelve articles of this special issue will be introduced.